Numerical modelling of multibeam accelerating structures - Gavrilov, N.M.; Komarov, D.A.; Bogachenkov, D.A.; Strukov, J.N. (Вопросы атомной науки и техники, 2004)
The three-dimensional multibeam numerical simulation has been carried out on the basis of integral equations.
Dispersion equations and expressions for shunt impedance and Q-factor have been obtained for E and H oscillations
in cylindrical cavities. The tensor Green function and filament-like representation of the beam were used. На основі методу інтегральних рівнянь проведене тривимірне чисельне моделювання
багатопроменевих прискорюючи структур. Для Е- и Н- резонаторів при використанні нитковидного
зображення струму джерела і тензорної форми функції Гріна для циліндричного резонатора отримані
дисперсійні рівняння, вирази для шунтового імпедансу і добротності. На основе метода интегральных уравнений проведено трехмерное численное моделирование
многолучевых ускоряющих структур. Для Е- и Н- резонаторов при использовании нитевидного
представления тока источника и тензорной формы функции Грина для цилиндрического резонатора
получены дисперсионные уравнения, выражения для шунтового импеданса и добротности.